SOCIOLINGUISTICS AND THE HISTORY OF ENGLISH: A SURVEY - Nevalainen, Terttu; Raumolin-Brunberg, Helena (International Journal of English Studies, 2009)
The English language has a well-documented history which can be traced back over twelve hundred years. This paper discusses the history of English focussing on the evidence it offers for sociolinguistic inquiry and raising issues to do with the social, historical and empirical validity of the enterprise. As the documentation on the earliest stages of the language is fragmentary, little sociolinguistic variation can be reconstructed on the basis of it. However, the Anglo-Saxon period (c. 700-1 100) does provide material for the study of the sociology of the multilingual language community. From c. 1400 onwards, the opportunities gradually improve to relate linguistic variation to speaker variables such as regional background, social status and gender. The wealth of data preserved from the Late Modem English period (1 700- 1900) enables even the reconstruction of the writers’ social networks on an empirical basis.